Credit utilization pattern and repayment behavior of the fish farmers in Mymensingh and Kishoreganj districts - Mondal, MAH; Ali, MM; Shamsuddin, ABM (Journal of the Bangladesh Agricultural University, 2013)
The study was conducted to assess the credit utilization pattern and repayment behavior of the fish farmers in Mymensingh and Kishoreganj districts during January to December, 2009. Data were collected from 600 fish farmers, 300 each from each district by employing stratified random sampling technique. Credit utilization rate in Mymensingh district was 49.04%, 56.73% and 70.29% in case of small, medium and better-off farmers, respectively. In Kishoreganj district, small, medium and better-off farmers utilized their credit money to the extent of 48.02%, 56.12% and 57.08%, respectively. Fifty eight percent of the credit money was utilized for aquaculture purpose. Credit repayment rate was 96% in both the two districts and the small farmers were found to be better re-payers than the others. Weekly repayment system was found to be the major hindering factor for timely repayment of credit. Utilization and repayment behavior of credit money were almost satisfactory after phasing out of the MAEP project. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14928 J. Bangladesh Agril. Univ. 10(2): 349-354, 2012